2021
DOI: 10.1155/2021/3466757
|View full text |Cite
|
Sign up to set email alerts
|

The Hydroethanolic Stem Bark Extract of Tieghemella heckelii (A.Chev.) Pierre ex Dubard (Sapotaceae) Produced N-Methyl-D-Aspartate (NMDA) Receptor-Dependent Analgesia and Attenuates Acute Inflammatory Pain via Disruption of Oxidative Stress

Abstract: Background. Tieghemella heckelii stem bark is used in African traditional medicine to treat inflammatory pain conditions. However, these biological actions of the plant have not been proven. This study investigates the phytochemical composition and the mechanisms of analgesic and anti-inflammatory actions of the hydroethanolic stem bark extract of T. heckelii (THBE). Methods. Phytochemical composition of THBE was investigated using qualitative and quantitative phytochemical analyses. Anti-inflammatory activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
(45 reference statements)
0
7
0
Order By: Relevance
“…Studies have shown that an effective in vitro DPPH free radical scavenging capacity of a plant extract indicates a corresponding in vivo anti-oxidant potency (Kumatia et al, 2021b;Kumatia et al, 2021c). Therefore, ASE and ASEA may also be very effective anti-oxidant agents in vivo which contributes to its anti-arthritic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that an effective in vitro DPPH free radical scavenging capacity of a plant extract indicates a corresponding in vivo anti-oxidant potency (Kumatia et al, 2021b;Kumatia et al, 2021c). Therefore, ASE and ASEA may also be very effective anti-oxidant agents in vivo which contributes to its anti-arthritic activity.…”
Section: Discussionmentioning
confidence: 99%
“…The central analgesic effect of opioid analgesics is mediated by their effect on opioid receptors. [ 26 27 ] The antipyretic action of DDB could be due to a reduction in prostaglandin levels and pro-inflammatory mediators. [ 25 ]…”
Section: Discussionmentioning
confidence: 99%
“…Pain results from acute inflammatory processes which stimulate sensory neurons through mediators related to inflammation such as, prostacycline, prostaglandine, histamine, thromboxane, prostaglandins, substance P, bradykinins, and cytokines released after cell injury. This pain signal is then amplified and transmitted leading to clinical pain states and central sensitization (Kumatia et al, 2021). The constriction of abdominal muscles, extension of the forelimbs, and elongation of the body occurs due to release of several endogenous inflammatory mediators which induce visceral pain.…”
Section: Discussionmentioning
confidence: 99%
“…Analgesic activity depends on the interruption of neuropeptides, inflammatory mediators, and or neurotransmitters used in the perception and transmission of pain, and Non-Steroidal Anti-Inflammatory (NSAIDS) inhibit various chemicals to achieve this goal. This includes, inhibition of mediators such as cyclooxygenase (COX) and therefore reduced release of prostaglandins (PGs) (Kumatia et al, 2021, Tewari et al, 2021.…”
Section: Discussionmentioning
confidence: 99%